Vertebrate endemism in south-eastern Africa numerically redefines a biodiversity hotspot - Perera, Sandun J.; Procheş, Şerban; Ratnayake-Perera, Dayani; Ramdhani, Syd (Zootaxa, 2018)
We use numerical methods to explore patterns of vertebrate endemism in south-eastern Africa, refining the boundaries of the intuitively-defined Maputaland-Pondoland-Albany biodiversity hotspot, also proposing a zoogeographic regionalisation. An incidence matrix of 300 vertebrate species endemic to south-eastern Africa sensu lato in 37 operational geographic units were used in (a) phenetic cluster analysis (PCA) using the algorithm of unweighted pair-group method with arithmetic averages (phenetic approach), and (b) parsimony analysis of endemicity (PAE; parsimony approach), in order to numerically evaluate the bioregional delimitations. The analyses provide a valid biogeographical entity 37% larger than the Maputaland-Pondoland-Albany hotspot, but substantially (131%) higher in vertebrate endemicity viz. the Greater Maputaland-Pondoland-Albany (GMPA) region of vertebrate endemism. South-east Africa is recognised as a dominion in the global zoogeographical area hierarchy, with subordinate units including the GMPA province. Various spatially-based measures of endemism were mapped for vertebrate species restricted to the dominion, i.e. endemic to south-eastern Africa sensu stricto. Areas and centres of endemism detected respectively from PAE and PCA, within the south-east Africa dominion also support the refined boundary of the GMPA region of endemism, which provides a better spatial conservation priority compared to the Maputaland-Pondoland-Albany hotspot. Reptiles and amphibians are found to be the main drivers of the overall pattern of endemism, while the pattern in freshwater fish is the most distinctive. Our analyses also indicate a good congruence of the centres of endemism across different terrestrial vertebrate taxa.